2022
DOI: 10.3390/brainsci12030309
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Electroencephalogram Records Simultaneous Subdural Electrode-Detectable, Scalp Electrode-Undetectable Interictal Epileptiform Discharges

Abstract: Introduction: We hypothesized that an endovascular electroencephalogram (eEEG) can detect subdural electrode (SDE)-detectable, scalp EEG-undetectable epileptiform discharges. The purpose of this study is, therefore, to measure SDE-detectable, scalp EEG-undetectable epileptiform discharges by an eEEG on a pig. Methods: A pig under general anesthesia was utilized to measure an artificially generated epileptic field by an eEEG that was able to be detected by an SDE, but not a scalp EEG as a primary outcome. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In many cases, a standard metal guidewire was advanced to the recording location and a standard catheter was used to insulate the entire length except for a few millimeters at the end, producing a single electrode at the tip [23,53]. In some cases, custom insulated guidewires with exposed metal electrodes [15,16,19,24,[46][47][48][49][50][51] or catheters with embedded electrodes [25,52] were built specifically for recording purposes (rather than using existing guidewires, which were not insulated, or existing catheters, which did not contain electrode sites). Guidewire-and catheterlike devices used for endovascular recording typically range from 0.2 to 0.6 mm in diameter with a 1.5-60 mm exposed tip (electrode) length [15,19,[22][23][24][25].…”
Section: Types Of Endovascular Recording and Stimulation Devices 321 ...mentioning
confidence: 99%
See 3 more Smart Citations
“…In many cases, a standard metal guidewire was advanced to the recording location and a standard catheter was used to insulate the entire length except for a few millimeters at the end, producing a single electrode at the tip [23,53]. In some cases, custom insulated guidewires with exposed metal electrodes [15,16,19,24,[46][47][48][49][50][51] or catheters with embedded electrodes [25,52] were built specifically for recording purposes (rather than using existing guidewires, which were not insulated, or existing catheters, which did not contain electrode sites). Guidewire-and catheterlike devices used for endovascular recording typically range from 0.2 to 0.6 mm in diameter with a 1.5-60 mm exposed tip (electrode) length [15,19,[22][23][24][25].…”
Section: Types Of Endovascular Recording and Stimulation Devices 321 ...mentioning
confidence: 99%
“…In some cases, custom insulated guidewires with exposed metal electrodes [15,16,19,24,[46][47][48][49][50][51] or catheters with embedded electrodes [25,52] were built specifically for recording purposes (rather than using existing guidewires, which were not insulated, or existing catheters, which did not contain electrode sites). Guidewire-and catheterlike devices used for endovascular recording typically range from 0.2 to 0.6 mm in diameter with a 1.5-60 mm exposed tip (electrode) length [15,19,[22][23][24][25]. Although there are some publications reporting stimulation, the primary focus in most research with guidewire or catheter electrodes was recording.…”
Section: Types Of Endovascular Recording and Stimulation Devices 321 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that eEEG can detect the epileptic discharges detected by subdural electrodes in experiments using a pig animal model [ 23 ]. The previous experiment [ 23 ] placed the eEEG electrode in the superior sagittal sinus, not allowing clarification of whether lateralization can be judged.…”
Section: Introductionmentioning
confidence: 99%